Typification of names in the genus Bouchea (Duranteae, Verbenaceae) - Moroni, Pablo; O’leary, Nataly (Phytotaxa, 2017)
Based on the ongoing taxonomic studies of the genus Bouchea and with the aim of contributing to stabilize its nomenclatural framework, ten names actually belonging to Bouchea were identified to need typification or proper typification remarks. As a result the names B. agrestis, B. ehrenbergii, B. linifolia, B. rusbyi and B. spathulata are lectotypified, a neotype is selected for the name Stachytarpheta pseudochascanum (≡ B. pseudochacanum) and the name Verbena fluminensis (≡ B. fluminensis) is epitypified. Updates and supporting information for three names already typified by Harold Moldenke in the year 1940 are provided: Valerianoides boliviana (≡ B. boliviana), B. dissecta and B. pseudogervao f. pilosa.